2011
DOI: 10.1007/s00384-011-1394-2
|View full text |Cite
|
Sign up to set email alerts
|

Sacral nerve modulation in the treatment of chronic pelvic pain

Abstract: Sacral neuromodulation proved to be effective in the treatment of some patients affected by chronic pelvic pain, and the effect persists over time. A positive screening phase and a positive response to gabapentin or pregabalin showed to be predictors of a successful response. Multiple localizations of pelvic pain and pain occurred after stapler surgery seem to be negative factors for the success of the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 30 publications
1
36
1
2
Order By: Relevance
“…Finally, neuropathic pain associated with the incisional scar, as well as visceral pain traits reflected by presence of deep abdominal and pelvic pain (often related to uterine contractions), have been suggested to develop and even coexist in patients undergoing obstetric interventions (Landau et al 2013; Lavand’homme 2013). Interestingly, afferent transmission modulation by epidural analgesia (Bouman et al 2014) or sacral nerve stimulation (Martellucci et al 2012) efficiently reduces the incidence of chronic postsurgical pain, including deep pain. However, it remains to be established what is the relative effect of epidural analgesia or sacral nerve stimulation over visceral vs. non-visceral afferents.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, neuropathic pain associated with the incisional scar, as well as visceral pain traits reflected by presence of deep abdominal and pelvic pain (often related to uterine contractions), have been suggested to develop and even coexist in patients undergoing obstetric interventions (Landau et al 2013; Lavand’homme 2013). Interestingly, afferent transmission modulation by epidural analgesia (Bouman et al 2014) or sacral nerve stimulation (Martellucci et al 2012) efficiently reduces the incidence of chronic postsurgical pain, including deep pain. However, it remains to be established what is the relative effect of epidural analgesia or sacral nerve stimulation over visceral vs. non-visceral afferents.…”
Section: Discussionmentioning
confidence: 99%
“…However a number of publications stated the ability of such stimulation to relieve pain, as well as relieving voiding symptoms in pelvic pain patients treated for coinciding pelvic dysfunction [18][19][20][21]. This is the first study demonstrating the effectiveness of CSRN in the management of CPPS in patients refractory to conventional treatment or only partially responding to continuous sacral nerve stimulation, with more than 85% improvement in naïve patients and up to 77% in patients already implanted.…”
Section: Discussionmentioning
confidence: 87%
“…VAS scale, McGill and SF-36 questionnaires improved consistently in all domains and patients reported an overall satisfaction rate of 95% when asked if they could recommend this therapy to a friend or a relative [18][19][20][21]. Tables 2 and 3 Table 3: Implanted patients, Pain and QoL evaluation in 7 previously implanted patients.…”
Section: Resultsmentioning
confidence: 96%
“…In some studies, sacral stimulation application is observed to provide sufficient pain control in patients with anorectal pain (18,19). Martellucci et al (20) argued that sacral stimulation is effective in patients with various chronic pelvic pains, and that an effective response to pregabalin and gabapentin can be a predictive factor for successful treatment; in addition, the use of surgical staples may negatively impact the result. In a systematic research, neurostimulation applications are recommended to be effective, safe, and, in the long term, profitable treatments in chronic pelvic pain and bladder pain (21).…”
Section: Painmentioning
confidence: 99%